The Influence of Own-Source Revenue, Transfer Funds, Regional Fiscal Capacity, And Capital Expenditure On Regional Loans - YULSIATI, Henny; SARTIKA, Iin; FEBRIANTOKO, Jovan (Journal of Governance, Taxation and Auditing, 2025)
This study aims to examine the effect of Own-own Source Revenue, Transfer Funds, Regional Fiscal Capacity, and Capital Expenditure on Local Government Loans in districts and cities across Sumatra. Employing a quantitative framework, the research is based on secondary data derived from regional budget realization reports together with fiscal capacity indices, and the data were selected through purposive sampling, resulting in 215 observations from 43 local governments during the 2019–2023 period. Panel data regression analysis was performed using EViews version 12. The results show that PAD and Transfer Funds have no significant effect on Local Government Loans. In contrast, Fiscal Capacity and Capital Expenditure show a statistically proven beneficial impact. Simultaneous testing confirms that all independent variables jointly influence Local Government Loans. These findings indicate that high capital expenditure and strong fiscal capacity encourage local governments to utilize loans as an alternative financing source for infrastructure development. Meanwhile, high transfer funds and PAD do not necessarily influence borrowing decisions. The study concludes that strengthening fiscal capacity and strategic planning of capital spending are crucial for promoting productive and sustainable local borrowing.